Concurrent Eosinophilic Solid and Cystic Renal Cell Carcinoma and Angiomyolipoma With Epithelial Cysts in the Setting of Tuberous Sclerosis Complex: A Rare Synchronous Occurrence of 2 Distinct Entities. (October 2019) - Cho, Woo Cheal; Collins, Katrina; Mnayer, Laila; Cartun, Richard W.; Earle, Jonathan S.
Eosinophilic solid and cystic renal cell carcinoma (ESCRCC) is a recently described distinct renal neoplasm known to occur almost exclusively in female patients with or without tuberous sclerosis complex (TSC). We report a case of ESCRCC with 2 synchronous angiomyolipomas, including 1 angiomyolipoma with epithelial cysts (AMLEC), a rare cystic variant of AML that typically arises sporadically in the absence of TSC, in a 46-year-old woman with TSC. Besides additional copy number alterations identified in ESCRCC via molecular karyotyping, we also report a unique histologic feature of TSC-associated ESCRCC previously not described in detail, with formation of semicircular multinucleated neoplastic giant cells engulfing an additional intact neoplastic cell, simulating emperipolesis. To the best of our knowledge, this is the first reported case of ESCRCC with concurrent AMLEC in a patient with TSC, confirmed through additional genetic testing showing a germline heterozygous mutation in TSC1 . Awareness of ESCRCC helps avoid the pitfall of a diagnosis of unclassified renal cell carcinoma, a typically much more aggressive tumor.